THE PSYCHOLOGICAL ASPECTS OF THE MAIN CHARACTERS OF ROBERT ZEMECKISâ€™ MOVIE â€œFORREST GUMPâ€ - Musyrifah Mahfuddin; Budiarti Putri Uleng (Jurnal Andi Djemma | Jurnal Pendidikan, 2023)
The purpose of this study was to learn about the psychological aspects of the main characters in the film "Forrest Gump" by Robert Zemeckis. The descriptive method was used in this study. The main data came from the movie "Forrest Gump," and the secondary data came from some literature related to the subject of the research. The data were analyzed using by descriptive method.The result of the study showed the psychological aspects of the main characters that had been analyzed. Forrest Gump was stupid, foolish, limited in terms of intellectual development. He was sad, anxious, friendly, and happy in terms of emotional development. He was patient and generous in terms of personality development. He was good in terms of morality development. Jenny was clever and connect in terms of emotional development. She was annoyed, happy, regret, and friendly in terms of emotional development. She was good in term morality development. She was covert in term of personality. Mrs. Gump was clever and connect in terms of intellectual development. She was happy and sad in terms of emotional development. She was generous and strong in terms of personality development. She was approximately in term morality.